(untitled) (Quest Journal of Management and Social Sciences, 2021)
Background: The workplace is a complex and cultured environment that requires intellectual leadership and a different degree of management style due to global economic competitiveness. Objective: The objectives of the study are to examine the relationship between leadership style, organizational culture, and job satisfaction among workers in the Agricultural and Rural Management Training Institute (ARMTI) Ilorin, Kwara State, Nigeria. Method: This research study employed a descriptive survey research method. The total number of employees in ARTMTI in Ilorin was 762. Using a simple random sampling technique, a total of 401 respondents was randomly selected from the population of the study for questionnaire administration. 401 questionnaires were distributed out of which 325 questionnaires were retrieved and analyzed for the study. Data were analyzed using Pearson Moment Correlation on the relationships between leadership style, organizational culture, and job satisfaction. Result: The study found that leadership style and organizational culture were significantly correlated with job satisfaction at a 0.05 level of significance. Conclusion: Based on the findings of the study, the study concluded that there is a relationship between leadership style, organizational culture, and job satisfaction among workers in the Agricultural and Rural Management Training Institute (ARMTI) Ilorin, Kwara State, Nigeria. Recommendation: The study recommended that leaders should realize that influencing the satisfaction of employees leads to higher performance and lower turnover rates among other things. Leadership in organizations should be assessed and managers should become aware of what is needed to obtain positive results from employees to improve performance. Originality: This article is original and there is no potential conflict of interest.